(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This examine become confirmed to look at impact of mushroom supplementation as a prebiotic compound in fed diets of enhancement of increase overall performance in Nile tilapia, (Oreochromis niloticus) on the aquaculture unit in laboratory. A general of fifty fishes (25 in keeping with water tank) with preliminary common frame weighted of 50.64 ± 0.0329 gram had been fed diets supplemented with 25% mushroom stalk experimental food plan (MSEF) and market available food plan (MAF) for seven weeks in cage system. During the assessment, the physico-chemical parameters of used water had been maintained normal range for optimal growth. The effects confirmed the first-rate very last weight gains (WG) become discovered with inside the fish fed supplemented with 25% mushroom stalk experimental diet were suggestively accelerated as compared with fish fed market available food plan.